2018
DOI: 10.17576/jsm-2018-4706-18
|View full text |Cite
|
Sign up to set email alerts
|

Najis (Tinja) Manusia daripada Perspektif Sains dan Islam serta Amalan Pemakanan Sunnah

Abstract: Islam merupakan satu agama yang menitikberatkan kesihatan manusia termasuklah sistem pencernaan manusia. Najis (tinja) manusia yang dibincangkan dalam kajian ini merupakan hasil buangan manusia yang menjadi salah satu kaedah untuk melihat sudut kesihatan manusia. Objektif penyelidikan ini ialah untuk mengkaji fizikokimia dan ciri-ciri najis serta kegunaannya daripada perspektif sains dan sudut pandangan Islam terutamanya mengenai diet yang diamalkan oleh Rasulullah SAW. Kajian ini dijalankan dengan menggunakan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Jaafar & Raus (2014), in their investigation, which concentrated on the methods and implications of the implementation of al-Quran and Hadith studies in several mosques around Nilai and the Federal Territory of Kuala Lumpur, found that this type of study received a satisfactory response. Factors that help stimulate community response are the uniqueness of the Quran and Hadith (Kashim et al, 2018). In addition, the mosque's position, delivery techniques and management also decide the community response.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jaafar & Raus (2014), in their investigation, which concentrated on the methods and implications of the implementation of al-Quran and Hadith studies in several mosques around Nilai and the Federal Territory of Kuala Lumpur, found that this type of study received a satisfactory response. Factors that help stimulate community response are the uniqueness of the Quran and Hadith (Kashim et al, 2018). In addition, the mosque's position, delivery techniques and management also decide the community response.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A modern food product produced from halal animals is deemed halal ( Husni et al, 2015 , Kashim et al, 2018a , Kashim et al, 2018b ). Following this principle, any food produced through biotechnological processes to cater to the modern Islamic community should first assess the permissibility (halal or haram) of the types of animals that form the basis or foundation of the developed food product ( Husni et al, 2012 ).…”
Section: Islamic Perspective On Animal Cloningmentioning
confidence: 99%
“…Islam naturally underscores the obligation to obey all the rulings written in the Quran and the Sunnah as commanded by Allah SWT. Power and following duties are rendered to leaders legally appointed to lead and govern the country with complete trust and justice (Kashim et al, 2018). As an ordinary human being, life will not be complete and well-managed without a robust and sovereign leader (Azhariah, 2010).…”
Section: Introductionmentioning
confidence: 99%